PENYELESAIAN PIUTANG AKAD MURABAHAH MENURUT FATWA DSN NOMOR 47 TAHUN 2005: STUDI PADA BANK SYARIAH INDONESIA KCP LHOKNGA ACEH BESAR - Ghina Putri Raihan; Husni Abdul Jalil (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2024)
This article aims to analyze the practice of settling murabaha receivables at BSI KCP Lhoknga with a study of Fatwa DSN-NO 47 of 2005. The fatwa provides guidance on sharia principles that must be adhered to in the settlement of murabaha receivables. The analysis is carried out on banking practices in settling murabaha receivables in community life. The aim is to ensure the development of an Islamic banking system that is free from usury. Because at this time there are still many people who think that Islamic banking and conventional banks are the same. This research is written with a conceptual approach, the type of research conducted in writing this scientific work uses a qualitative form, namely data collection in a scientific setting using scientific methods and conducted by scientifically interested people or researchers. The data used are primary data and secondary data. Primary data is obtained from interviews and observations. The results showed that the practice of settling murabahah receivables at BSI KCP Lhoknga seen from the review of DSN-MUI fatwa No. 47 of 2005 discusses the settlement of murabahah receivables for customers who are unable to pay, and the fatwa provides settlement requirements that must be followed as well as the responsibilities of customers and LKS to carry out settlements in accordance with the provisions in the fatwa. Therefore, the settlement practice has complied with the commandments of sharia principles including fairness and transparency in determining the amount of debt that must be paid by the debtor, and the fatwa which also regulates procedures when settling debts in situations of late payment or inability to pay. So, basically this contract is a direct agreement where the desired profit is predetermined. Fatwa DSN-NO 47 of 2005 explains that the settlement must be complied with, such as the object of collateral being sold by the customer at an agreed price and then the customer paying off the remaining forest to the Islamic financial institution (LKS) from the proceeds of the sale.